2015
DOI: 10.1097/meg.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and behaviour about smoking among inflammatory bowel disease patients

Abstract: The majority of IBD patients are unaware of the effects of tobacco on their disease. Better information through a therapeutic education programme should be systematically recommended in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…16,18 Studies in non-IBD populations have found that smoking initiation is more likely when there is a perceived short-term benefit, despite acceptance of short-and long-term risks. Furthermore, we found no evidence that smoking cessation impacts adversely on subsequent clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16,18 Studies in non-IBD populations have found that smoking initiation is more likely when there is a perceived short-term benefit, despite acceptance of short-and long-term risks. Furthermore, we found no evidence that smoking cessation impacts adversely on subsequent clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, more recent studies have not supported this finding. 16 The wider health benefits of smoking cessation are beyond dispute 17 but its impact on clinical outcomes in UC is poorly understood. 14 These findings were at odds with a prior meta-analysis, using different inclusion criteria, which found smoking to be associated with reduced risk of colectomy (OR 0.55, 95% CI 0.33-0.91).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most patients are not aware of the effects of smoking on their disease activity. In a questionnaire study, three-quarters of smokers knew that tobacco was not beneficial for their CD, whereas all UC patients were aware that smoking had a beneficial effect [51]. The intent to quit smoking was superior in informed patients compared with those who were uninformed.…”
Section: Introductionmentioning
confidence: 99%